Examination of wind speed based on field measurements on a low-rise building - Wang, Shuoqi; Reed, Dorothy A.; Lyman, Greg; Estephan, Johnny; Irwin, Peter; Chowdhury, Arindam (Frontiers in Built Environment, 2025)
Mean and peak wind speeds, as well as gust factors, integral scales, and intensity of turbulence values, are essential in formulating wind loading standards for structures. In recent years, the characterization of rooftop wind speeds has become more important when designing photovoltaic arrays. As part of an investigation into the wind loading and structural behavior of pedestal mounted photovoltaic arrays, wind speeds at two elevations were investigated through an analysis of field measurements performed at the Central Washington University campus in Ellensburg, Washington. Specifically, two roof-mounted R.M. Young ultrasonic anemometers were employed in the data collection project: one located at 21.9 m [72 ft] above ground, and the other, closer to a pedestal-mounted photovoltaic array, at 12.5 m [41 ft] above ground. The wind speeds measured by the 21.9 m elevation anemometer were examined with a view to ascertaining that they are not significantly affected by the Central Washington building sited near its location. This paper focuses on the examination of the wind speeds only. Results showed that the wind speeds measured by the 12.5 m elevation anemometer are significantly affected by the presence of the building and that significant resonant effects are induced for the photovoltaic panels. The results of this work make it possible to adopt Japanese structural design practice wherein the design is performed for wind effects induced by 10-min, rather than by 60-min wind speeds as in current U.S. practice, thereby significantly reducing computation times. The results presented in this work also allow for the rigorous determination of 10-min speeds as functions of peak 3-s gusts. Estimates of integral scales of turbulence were shown to be characterized by large uncertainties, on the basis of which it is possible to obtain coefficients of variation required for determining the magnitude of wind load factors used in practice.